Prudence or Profligacy: Deficits, Debt, and Fiscal Consolidation. - Boltho, A; Glyn, A (2006)
Over the last quarter century, public finances have been under pressure in most OECD countries as deficits and debts rose under the pressure of relatively slow growth and high interest rates. This, in turn, has affected the welfare state, since efforts at containing deficits have often been concentrated on public expenditure. Much of the literature argues that this is desirable, since curbing deficits via tax increases seldom succeeds. A medium-term survey of OECD country experience suggests a less clear-cut conclusion. In a number of countries which were able to curb debt/GDP ratios, the bulk of the adjustment did, indeed, come from spending cuts (but was, also, in some cases helped by rapid growth and/or currency depreciation). In several, however, tax increases also appear to have succeeded in reducing deficits and debt.